PERAN KELENGKAPAN IMUNISASI DASAR DALAM TUMBUH KEMBANG ANAK USIA 1 – 3 TAHUN DI POSYANDU DEWI SAWITRI KARTASURA - Ratna Indriati; Anita Silvia Anggraini (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2018)
Background: Child development is a very important part. The percentage of underweightunder five years of age in Indonesia at 2017 was 17.8%. Children's vulnerability to thedisease can affect children's growth can be reduced either by giving immunizations.Children who get complete immunization will have strong immunity and becoming healthychildren, where the conditions favor the optimal development of the child. At PosyanduDewi Sawitri there are children immunized incomplete and growth are not in accordancewith his age.Purpose and benefit: To determine the role of complete basic immunization in childdevelopment. The benefits of the research are highlighted the importance of a completebasic immunization in children as one of the efforts to promote growth and developmentof children.The subject of study: 56 children aged 1-3 years in Posyandu Dewi Sawitri Kartasura.Method Research of analytical observation, correlation design with cross sectionalmethod. Sampling is purposive sampling. The data obtained were analyzed with ChiSquare test with p = 0.05.The Result of Research: Have shown that children with a complete basic immunization of40 children (71.4%), did not complete 16 children (28.6%). Children with optimal growthof 37 children (66.1%), is not optimal 19 children (33.9%). Children with developmentalcorresponding 46 children (82.1%), do not fit in 10 children (17.9%). The results of theanalysis of complete basic immunization role in the growth of children using Chi Squaretest was obtained p = 0.026 (p <0.05), which means Ha accepted, and role in childdevelopment obtained p = 0.001 (p <0.05), which means Ha accepted.Conclusion: Complete basic immunization role in growth and development of the child.Keywords: Completeness of immunization, child development, child growth